PIDANA PENGAWASAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM DALAM SISTEM PEMIDANAAN DI INDONESIA - Alifa Rizqi Fajriani; Muridah Isnawati (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2022)
This study focuses on examining criminal oversight of children in conflict with the law in the Indonesian criminal system, the trend of increasing rates of juvenile delinquency and the level of offenses committed by minors which lead to crimes committed by children which encourages more supervision. Providing appropriate direction, countermeasures, or handling for children who commit violations that lead to criminal acts. This study uses the Statute Approach. The results of the study show how the juvenile criminal law policy regarding criminal supervision of children in conflict with the law.